Pengujian Black Box Testing Pada Aplikasi Absensi Berbasis Web Di Sekolah SDN Duri Kepa 01 - Nina Amelia Silitonga; Luthfi Hanan Dio Samartha; Tabah Adi Wiguna; Muhammad Baidawi; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Absences are evidence of a presence in the reporting activities of each institution. In the context of education, absenteeism is used as a medium for recording who are the students or students who are present in class. However, the outbreak of coronavirus in Indonesia has resulted in the learning process being carried out online by utilizing online media for learning, including in recording attendance. SDN Duri Kepa 01 is one of the schools that implements an online attendance system using google forms to record the absences of teachers, staff and students during the Covid-19 pandemic. The use of google forms in the attendance system is considered inefficient, therefore it is necessary to design an application for absenteeism that can make it easier for school residents of SDN Duri Kepa 01. In this application, it is necessary to design an attendance system by utilizing advances in information systems and computer technology. The research method used is Black Box Testing, where testing is carried out to observe the results of inputs and outputs from software. The implementation of this system uses Web-based technology using PHP, HTM and CSS. This test was carried out to overcome the problem of attendance systems that previously used google forms to be web-based. With this system, it is easier for teachers and students to carry out attendance activities, and staff are also easy to recapitulate existing attendance accurately and instantly.